PELATIHAN KEAMANAN SISTEM INSTALASI KABEL TANAM DI DESA MELINGGIH KECAMATAN PAYANGAN-GIANYAR - I.N. Budiastra; C.G.I. Partha; I.G.D. Arjana; I.B.A. Swamardika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Electricity is a very vital needs for the life of the community it is today. Electricity became the primary needsof the relatively inexpensive price because in addition is also very helpful in everyday life. In addition toelectricity has huge advantages, electricity also has a hazard that can lead to accidents such as fire, electricalcurrent was stung and damage electrical equipment. Bali is an island of the gods and the visit of a veryfamous Tourism both locally and internationally. The beauty of Bali we must keep together in order to lookmore natural. Lighting is one of the effects of the sun rays create the beauty of being a more natural look. Theplacement of the lights as the lighting to create a natural atmosphere, usually placed on top of or below,because the light on the object is not interrupted. Because of the Permasalahn above, then the electricalinstallation has also become very influential for aesthetics, so the installation is generally ditanan in theground. The main constraint in the system in the ground is a way to install and secure the conductor. Of these problems this devotion will provide information about the security system wiring installation. Electricalhazards can be eliminated by following all electrical installation requirements. Danger of electric shock andfires can be corrected with electrical installation safety contained in the 2011 electrical installation Generalrequirements (Amendment 2011serta year 2014 PUIL, who hinted to secure the environment in this securinghuman safety, mandatory use of electrical installation in accordance with the National Standard safetyIndonesia (SNI). In this devotion will be given explanations and Training Security System Installation Cableplant in the village of Payangan Gianyar-Melinggih Sub-district, which provide devotion often occur becauseof electrical interference system wiring and equipment who do not meet the requirements of the electricalinstallation.